Purification and characterization of an alpha-bungarotoxin receptor that forms a functional nicotinic channel. - Gotti, C (1991)
Neither the structure nor the function of alpha-bungarotoxin (alpha Bgtx) binding molecules in the nervous system have yet been completely defined, although it is known that some of these molecules are related to cation channels and some are not. Using an improved method of affinity chromatography, we have isolated a toxin binding molecule from chicken optic lobe that contains at least three subunits with apparent Mr values of 52,000, 57,000, and 67,000. The Mr 57,000 subunit binds alpha Bgtx and seems to be present in two copies per receptor. The receptor is recognized by antibodies raised against the alpha Bgtx receptors of human neuroblastoma cells, fetal calf muscle, and chicken optic lobe but not by antibodies raised against Torpedo acetylcholine receptor, the serum of myasthenic patients, or monoclonal antibody, 35. 125I-labeled alpha Bgtx binding to the isolated receptor is blocked, with the same potency, by nicotinic agonists and antagonists, such as nicotine, neuronal bungarotoxin and, d-tubocurarine. When reconstituted in a planar lipid bilayer, the purified alpha Bgtx receptor forms cationic channels with a conductance of 50 pS. These channels are activated in a dose-dependent manner by carbamylcholine and blocked by d-tubocurarine.